Liquid crystal cream with ice cream appearance and preparation method thereof
By using a combination of carbomer sodium and sodium polyacrylate grafted starch, a liquid crystal cream with ice cream mousse texture is formed, which solves the problem of high viscosity and poor fluidity of liquid crystal emulsifiers in skin care products, and achieves product stability Improve skin feeling, enhancing moisturizing and anti-wrinkle effects.
Patent Information
- Application Number
- CN202411326984.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-02-07
AI Technical Summary
Liquid crystal emulsifiers are prone to high apparent viscosity and poor fluidity in skin care products, which affects the stability and skin feeling of the preparation system.
The combination of carbomer sodium and sodium polyacrylate grafted starch is used as a thickener and emulsifier. By combining the viscosity and hardness of the cream, it forms an ice cream mousse-like liquid crystal cream, and through layered liquid crystal technology and The polymer forms particulate gels, enhancing the stability and transport efficiency of the active ingredients.
It forms a light and non-greasy feeling, improves the heavy and dull feeling of traditional creams, improves the moisturizing, soothing, firming and anti-wrinkle effects of the product, and maintains stability in high and low temperature environments.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a liquid crystal cream with an ice cream appearance and a preparation method thereof, and relates to A61K, and in particular to the field of skin care products. Background Art
[0002] In the field of modern skin care, skin care products that are both highly effective and pleasant to use are increasingly gaining favor among consumers. Liquid crystal emulsification systems, due to their unique ordered and fluid structural characteristics, can optimize the stability and transmission efficiency of active ingredients and achieve the deep nourishing effect of skin care products. From the perspective of skin physiology, liquid crystal emulsification systems strengthen the skin barrier function by simulating the lipid structure between stratum corneum cells, which helps to enhance the skin's own defense mechanism and moisture retention ability, thereby promoting skin health. However, when liquid crystal emulsifiers are applied to skin care products, especially cream products, they are prone to problems such as high apparent viscosity and poor fluidity, which affect the stability and skin feel of the formulation system. Therefore, it is crucial to improve the stability of liquid crystal creams and enhance the pleasant skin feel.
[0003] Chinese invention patent CN202311714932.8 discloses a nano liquid crystal emulsion, its preparation method and application. The nano liquid crystal emulsion prepared by using liquid crystal emulsifier hydrogenated lecithin and phytosterol has the effect of locking in water and moisturizing. However, its emulsification system is relatively simple, and lecithin emulsifiers have the problems of poor water solubility and low HLB value. It is difficult for the prepared product to take into account both stability and skin feel. Summary of the invention
[0004] In order to improve the stability of liquid crystal cream in an ice cream state, the first aspect of the present invention provides a liquid crystal cream with an ice cream appearance. The preparation raw materials include, by weight percentage: 5-10% moisturizer, 0.1-1% preservative, 0.1-3% emulsifier, 15-25% emollient, 0.3-1% thickener, 1-5% skin conditioner, and water supplemented to 100%.
[0005] As a preferred embodiment, the moisturizing agent is selected from one or a combination of sugar moisturizing agents, polyol moisturizing agents, amino acid moisturizing agents, vitamin moisturizing agents, and lactate moisturizing agents.
[0006] As a preferred embodiment, the humectant is glycerin.
[0007] As a preferred embodiment, the emollient includes one or a combination of cetearyl alcohol, propylene glycol dicaprylate / dicaprate, myristyl stearate, pentaerythritol tetracocoate, squalane, polydimethylsiloxane, and vegetable oils.
[0008] As a preferred embodiment, the vegetable oil includes at least one of avocado tree (BUTYROSPERMUM PARKII) fruit oil and borage (BORAGO OFFICINALIS) seed oil.
[0009] As a preferred embodiment, the vegetable oil is avocado oil.
[0010] As a preferred embodiment, the emollient includes a combination of cetearyl alcohol, myristyl stearate, propylene glycol dicaprylate / dicaprate, squalane, polydimethylsiloxane, and avocado butter.
[0011] As a preferred embodiment, the weight ratio of cetearyl alcohol, myristyl stearate, propylene glycol dicaprylate / dicaprate, squalane, polydimethicone, and avocado butter is (0.1-1):(5-10):(1-5):(1-3):(1-3):(1-5).
[0012] As a preferred embodiment, the weight ratio of cetearyl alcohol, myristyl stearate, propylene glycol dicaprylate / dicaprate, squalane, polydimethicone, and avocado butter is (0.3-0.8):(7-9):(3-5):(1-2):(1-2):(3-5).
[0013] As a preferred embodiment, the weight ratio of cetearyl alcohol, myristyl stearate, propylene glycol dicaprylate / dicaprate, squalane, polydimethicone, and avocado butter is 0.5:8:4:2:1:4:.
[0014] As a preferred embodiment, the preservative is a combination of 1,2-hexanediol and p-hydroxyacetophenone.
[0015] As a preferred embodiment, the weight ratio of 1,2-hexanediol to p-hydroxyacetophenone is 0.5:0.5.
[0016] As a preferred embodiment, the thickener is selected from one or a combination of carbomer thickeners, polyacrylic acid thickeners, cellulose thickeners, and natural gum thickeners.
[0017] As a preferred embodiment, the carbomer thickener is sodium carbomer, and the polyacrylic acid thickener is sodium polyacrylate grafted starch.
[0018] As a preferred embodiment, the weight ratio of the sodium carbomer to the sodium polyacrylate grafted starch is (0.1-0.5): (0.1-0.5).
[0019] As a preferred embodiment, the weight ratio of the sodium carbomer to the sodium polyacrylate grafted starch is (0.15-0.5): (0.15-0.5).
[0020] As a preferred embodiment, the weight ratio of the sodium carbomer to the sodium polyacrylate grafted starch is 0.5:0.5 or 0.3:0.3 or 0.15:0.15.
[0021] During the experiment, the applicant found that a liquid crystal cream with an ice cream mousse texture can be formed by using a combination of sodium carbomer and sodium polyacrylate grafted starch. The possible reason is speculated to be: the viscosity and hardness of the cream are regulated by the compounding of sodium carbomer and sodium polyacrylate grafted starch to form a unique ice cream-like appearance and texture, and an obvious liquid crystal structure can be observed under a polarized light source. The uniform dispersion of the microparticle gel formed by the swollen sodium carbomer and sodium polyacrylate grafted starch helps to maintain the stability of the liquid crystal structure, and the microgel particles formed by the polymer have an internal cross-linked network structure and hydrophilic groups, which can improve the moisturizing effect of the liquid crystal cream, giving the cream product a light and non-greasy feel, as well as a cool and water-melting skin feel when applied. The applicant further discovered that the weight ratio of sodium carbomer and sodium polyacrylate grafted starch is 0.5:0.5, which can maintain the stability of the ice cream mousse texture while maintaining the liquid crystal structure. The possible reason is speculated to be: when the weight ratio of sodium carbomer and sodium polyacrylate grafted starch is maintained at 0.5:0.5, the liquid crystal structure can still be relatively well preserved, and the swollen polymer can form an ice cream-like appearance under the naked eye, the hardness and viscosity of the cream are appropriate, the performance is stable in high and low temperature environments, and there will be no problems such as abnormal viscosity, color oxidation, and odor deterioration.
[0022] As a preferred embodiment, the emulsifier is a combination of polyethylene glycol stearate and sorbitan stearate, and the polyethylene glycol stearate is selected from one or a combination of PEG-100 stearate, PEG-50 stearate, PEG-150 stearate, and PEG-200 stearate.
[0023] As a preferred embodiment, the emulsifier is a combination of PEG-100 stearate and sorbitan stearate.
[0024] As a preferred embodiment, the weight ratio of the PEG-100 stearate to sorbitan stearic acid is (0.3-0.9):(0.5-3).
[0025] As a preferred embodiment, the weight ratio of PEG-100 stearate to sorbitan stearic acid is (0.4-0.7):(1-2).
[0026] As a preferred embodiment, the weight ratio of PEG-100 stearate to sorbitan stearic acid is 0.6:1.05.
[0027] As a preferred embodiment, the skin conditioning agent includes glyceryl glucoside, panthenol and sweet tea (RUBUSSUAVISSIMUS) extract.
[0028] As a preferred embodiment, the weight ratio of the glyceryl glucoside, panthenol and sweet tea extract is (1-3): (1-3): (0.1-0.3).
[0029] As a preferred embodiment, the weight ratio of the glyceryl glucoside, panthenol and sweet tea extract is 1:1:0.1.
[0030] A second aspect of the present invention provides a method for preparing a liquid crystal cream having an ice cream appearance, comprising the following steps:
[0031] S1 Add water, moisturizer and preservative into the main pot, stir and heat to 80-85℃;
[0032] S2 Add emulsifier and emollient into the auxiliary pot, stir and heat to 80-85℃;
[0033] S3 adds the raw materials in the auxiliary pot into the main pot, adds thickener at the same time, and homogenizes at high speed;
[0034] S4 is cooled to 30-50℃, and skin conditioner is added until it is stirred evenly.
[0035] As a preferred embodiment, the high-speed homogenization rate in step S3 is 1000-5000 rpm, and the homogenization time is 5-10 min.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) The liquid crystal cream with the appearance of ice cream of the present invention adopts the combination of sodium carbomer and sodium polyacrylate grafted starch to form a liquid crystal cream with the texture of ice cream mousse (such as Figure 1 The ice cream mousse texture makes the product light and non-greasy, and it feels cool and hydrating on the skin when applied, which improves the heavy and dull feeling of traditional creams and provides a better sensory experience.
[0038] (2) In the liquid crystal cream with the appearance of ice cream described in the present invention, sodium carbomer and sodium polyacrylate grafted starch are used in a weight ratio of 0.5:0.5, which can form micro-gel when dispersed in an emulsified system. By adsorbing on the oil-water interface, it has a certain influence on the interaction force between droplets, stabilizes the emulsion state, and is also conducive to the formation of a liquid crystal structure.
[0039] (3) The liquid crystal cream with an ice cream appearance described in the present invention relies on lamellar liquid crystal technology and polymer to form microgels to enhance the stability and transmission efficiency of active ingredients, while simulating the structure of the skin lipid layer, strengthening the skin barrier function, and effectively improving the product's moisturizing, soothing, firming and anti-wrinkle effects on the skin. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is the product appearance of the cream in Example 1;
[0041] Figure 2 The liquid crystal morphology of the liquid crystal cream prepared in Example 1 under polarized light of a polarizing microscope;
[0042] Figure 3 The liquid crystal morphology of the liquid crystal cream prepared in Example 2 under polarized light of a polarizing microscope;
[0043] Figure 4 The liquid crystal morphology of the liquid crystal cream prepared in Example 3 under polarized light of a polarizing microscope;
[0044] Figure 5 The liquid crystal morphology of the liquid crystal cream prepared in Comparative Example 1 under polarized light of a polarizing microscope;
[0045] Figure 6 Polarized light micrographs of the liquid crystal cream prepared in Example 1 at -18°C, 25°C, 50°C and hot and cold cycle conditions; in the figure: upper left: 50°C; upper right: -18°C; lower left: 25°C; lower right: hot and cold cycle.
[0046] Figure 7 The facial skin redness images of subject No. 22 before and 28 days after using the product applied in Example 1; left: before use; right: after 28 days of use;
[0047] Figure 8 Ultrasound images of the skin of subject No. 29 before and 28 days after using the product applied in Example 1; left: before use; right: after 28 days of use;
[0048] Fig. 9 Images of under-eye wrinkles for subject No. 15 before and 28 days after using the product applied in Example 1; left: before use; right: after 28 days of use. DETAILED DESCRIPTION
[0049] Example
[0050] A liquid crystal cream with an ice cream appearance, the raw materials for its preparation are calculated by weight percentage as shown in Table 1 below.
[0051] Table 1
[0052]
[0053]
[0054] The polydimethylsiloxane was purchased from Dow (Zhangjiagang) Investment Co., Ltd. with the brand name XIAMETER TM PMX-200Silicone Fluid 2 cSt.
[0055] The sodium polyacrylate grafted starch was purchased from DAITO KASEI KOGYO CO., LTD., with the brand name MAKIMOUSSE.
[0056] The sweet tea extract was purchased from Ruwei Cosmetics Co., Ltd. The avocado butter was purchased from Cargill B.V., with the brand name Refined Shea butter-PC.
[0057] A method for preparing a liquid crystal cream with an ice cream appearance, comprising the following steps:
[0058] S1 Add water, moisturizer and preservative into the main pot, stir and heat to 83℃;
[0059] S2 Add emulsifier and emollient into auxiliary pot, stir and heat to 83℃;
[0060] S3: Add the raw materials in the auxiliary pot into the main pot, add thickener at the same time, and homogenize at 3000rpm for 10 minutes;
[0061] S4 is cooled to 40°C, and skin conditioner is added until it is stirred evenly.
[0062] Performance Testing
[0063] 1. Stability:
[0064] The stability of the samples was examined by accelerated tests. The test conditions were: 1 month at 50°C; 5 high and low temperature cycles (45°C and -18°C for 24 hours each, alternately); 1 month at -18°C; 3 months at 25°C. After the test, the samples were taken out and restored to 25°C to observe the sample status. The evaluation criteria are shown in Table 2. The test results are shown in Table 3.
[0065] Table 2
[0066] Points Rating Description 3 No adverse changes compared to the sealed samples stored at 25℃ 2 Minor imperfections that do not affect the basic properties of the formula 1 Serious defects (stratification, roughness), the formula cannot be used normally
[0067] Table 3
[0068]
[0069]
[0070] The test results show that Examples 1, 2, and 3 can all form a good ice cream appearance and texture, while Comparative Examples 1 and 2 cannot pass the stability test for each condition due to their low viscosity. Comparative Example 3 has a high content of thickener, and during the emulsification process, the viscosity is too high, making it difficult to disperse evenly, and thus cannot form a good ice cream appearance and texture.
[0071] 2. Microscopic observation of liquid crystal cream:
[0072] Use a spoon to take 2g of the sample, spread it on a clean glass slide, flatten it with a clean cover glass, and use an Olympus upright high-power microscope BX53M polarizing microscope to magnify 100 times to observe the prepared sample. First adjust and focus in the bright field until the microscopic particles can be seen clearly, and then observe the liquid crystal morphology, particle size and uniformity under polarized light. The test results of the liquid crystal cream of Examples 1-3 are shown in Figure 2-4 The test results of the liquid crystal cream of comparative example 1 are shown in Figure 5 .
[0073] The results show that the creams of Examples 1-3 can be observed to have obvious liquid crystal structures and a large number of black spherical substances under polarized light sources, which are presumably microgels formed by the swollen water-soluble polymer sodium carbomer and sodium polyacrylate grafted starch. Figure 2-4 As shown, with the increase of the concentration of water-soluble polymer, the microgel formed by the polymer in the system becomes more uniform, more stable, and has viscoelasticity. Although the liquid crystal is squeezed, the liquid crystal structure is still retained. Figure 5 In the comparative example 1, an obvious Maltese cross liquid crystal structure can be observed under a polarized light source. However, no water-soluble polymer is added to the system, and the stability of the cream is affected.
[0074] like Figure 6 As shown, after the cream of Example 1 has undergone high and low temperature cycles, its liquid crystal structure is slightly damaged and its brightness under polarized viewing field is reduced, but it still maintains a relatively high stability as a whole, especially under constant high temperature (50°C) and low temperature (-18°C) conditions.
[0075] The measurement was performed using an OLYMPUS BX53 microscope produced by Olympus Corporation at a magnification of 200 times.
[0076] 3. Efficacy test:
[0077] Healthy Chinese women aged 18-45 were recruited and 32 cases with sensitive skin (lactic acid stinging ≥ 3 points, TEWL ≥ 15 g / h / m 2) and have some signs of aging (skin sagging, wrinkles under the eyes level ≥ 2), apply the product used in Example 1 once in the morning and evening for 28 days. During the entire trial period, they cannot be exposed to the sun for a long time, engage in outdoor activities, etc., and must not change their daily life and facial care habits. They must not use cosmetics or medicines with similar efficacy to the product. Non-invasive testing of the cheek skin was performed before and 28 days after the test. Corneometer CM825 was used to test the moisture content of the stratum corneum. The larger the measured value, the higher the moisture content of the stratum corneum of the skin. The measurement unit is Corneometer Unit, abbreviated as CU. Tewameter was used TM Hex measures the transepidermal water loss (TEWL) of the skin. The smaller the value, the better the skin barrier. The measurement unit is g / h / m 2 . Ultranscan UC22 was used to measure the thickness and density of the epidermis and dermis of the skin. The larger the measured value, the greater the thickness and density. The thickness measurement unit is μm, and the density measurement unit is %. VISIA-CR image acquisition was used to analyze the changes in the percentage of wrinkle area under the eyes and the a* value of the skin red area before and after use of IPP. The smaller the value, the more obvious the improvement effect. Test environment: No direct sunlight, no wind, room temperature 21±1℃, humidity 50±10%RH.
[0078] 3.1 Moisturizing performance test: The test results are shown in Table 4.
[0079] Table 4
[0080]
[0081] After 32 subjects with sensitive skin used the samples for 28 days, the water content of the stratum corneum increased by 63.83% (p<0.001) and the transepidermal water loss decreased by 18.58% (p<0.001).
[0082] 3.2 Soothing effect test.
[0083] After using the product of Example 1 for 28 days, the a* value of the skin red area decreased by 8.27% (p<0.05), from 22.06±5.04 to 20.23±3.69. Figure 7 The facial red area image of subject No. 22 was collected for VISIA-CR, and it can be observed that the degree of skin redness of the subjects was significantly reduced.
[0084] 3.3 Firming and anti-wrinkle effect test.
[0085] Table 5
[0086]
[0087] After using the product of Example 1 for 28 days, the skin ultrasound diagnostic image results showed (as shown in Table 5, Figure 8 The thickness and density of the epidermis, as well as the thickness and density of the dermis, were significantly improved (P < 0.001). Fig. 9 As shown, the area ratio of under-eye wrinkles decreased significantly (P < 0.05), from 6.25 ± 3.13 to 5.45 ± 2.83, a decrease of 12.75%.
Claims
1. A liquid crystal cream with an ice cream appearance, characterized in that: The raw materials for preparation include, by weight percentage, 5-10% moisturizing agent, 0.1-1% preservative, 0.1-3% emulsifier, 15-25% emollient, 0.3-1% thickener, 1-5% skin conditioning agent, and water is added to 100%.
2. The liquid crystal cream with ice cream appearance according to claim 1, characterized in that: The moisturizing agent is selected from one or a combination of sugar moisturizing agents, polyol moisturizing agents, amino acid moisturizing agents, vitamin moisturizing agents, and lactate moisturizing agents.
3. The liquid crystal cream with ice cream appearance according to claim 1, characterized in that: The emollient includes one or a combination of cetearyl alcohol, myristyl stearate, pentaerythritol tetracocoate, propylene glycol dicaprylate / dicaprate, squalane, polydimethylsiloxane, and vegetable oils.
4. The liquid crystal cream with ice cream appearance according to claim 3, characterized in that: The vegetable oil comprises at least one of avocado oil and borage seed oil.
5. The liquid crystal cream with ice cream appearance according to claim 1, characterized in that: The thickener is selected from one or a combination of carbomer thickeners, polyacrylic acid thickeners, cellulose thickeners, and natural gum thickeners.
6. The liquid crystal cream with ice cream appearance according to claim 5, characterized in that: The carbomer thickener is sodium carbomer, and the polyacrylic acid thickener is sodium polyacrylate grafted starch.
7. The liquid crystal cream with ice cream appearance according to claim 6, characterized in that: The weight ratio of the sodium carbomer to the sodium polyacrylate grafted starch is (0.1-0.5): (0.1-0.5).
8. The liquid crystal cream with the appearance of ice cream according to claim 1, characterized in that: The emulsifier is a combination of polyethylene glycol stearate and sorbitan stearate, and the polyethylene glycol stearate is selected from one or a combination of PEG-100 stearate, PEG-50 stearate, PEG-150 stearate, and PEG-200 stearate.
9. A method for preparing the liquid crystal cream with the appearance of ice cream according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1 Add water, moisturizer and preservative into the main pot, stir and heat to 80-85℃; S2 Add emulsifier and emollient into the auxiliary pot, stir and heat to 80-85℃; S3 adds the raw materials in the auxiliary pot into the main pot, adds thickener at the same time, and homogenizes at high speed; S4 is cooled to 30-50℃, and skin conditioner is added until it is stirred evenly.
10. The method for preparing the liquid crystal cream with ice cream appearance according to claim 9, characterized in that: The speed of high-speed homogenization in step S3 is 1000-5000 rpm, and the homogenization time is 5-10 min.
Citation Information
Patent Citations
Nano liquid crystal emulsion as well as preparation method and application thereof
CN117731550A
Cited By
Composition, cold cream matrix and application thereof, cold cream and preparation method and application thereof
CN122461180A